The Multi-Social Relation of the Cattle Industry in the Plaosan Subdistrict Animal Market of Magetan Regency - Isbahi, Muhammad Baiqun; Zuana, Muhammad Mujtaba Mitra; Toha, Mohamad (Malacca: Journal of Management and Business Development, 2024)
As a legacy of the colonial era, the people of East Java have established cattle raising and development with four fundamental objectives in mind. To begin with, the cow signifies social standing. Social status in the local community is established not only by the financial resources of individual families, but also by the number of cows housed in a given pasture. Furthermore, the bovine serves as a support animal during the process of mating. The bovine is a sacred animal in East Java, representing matrimony to the local populace. Third, cows as economically beneficial animals. Furthermore, cattle are a commodity in which local economic authorities with vast business networks engage in commerce. Regarding cattle businessmen, this descriptive qualitative study seeks to investigate the socioeconomic networks of lower-class cattle producers who also practise subsistence agriculture. As qualitative research, this study collected field data through three primary methodologies. Initially, a comprehensive interview was undertaken with purchasers, the Magetan regency administration, and the local strong man business network. The second is the observation that was conducted in Plaosan subdistrict animal market and Dele villages in Magetan regency. Furthermore, an extensive focus group discussion (FGD) was conducted with stakeholders from the selling cycle, including local governments, businesses, cattle merchants, and the general community. This study's findings will be disseminated via scientific journals and local media.